Serological cross-reactivity among common flaviviruses - Chan, Kai Rol; Ismail, Amni Adilah; Thergarajan, Gaythri; Raju, Chandramathi Samudi; Yam, Hock Chai; Rishya, Manikam; Sekaran, Shamala Devi (Frontiers in Cellular and Infection Microbiology, 2022)
The Flavivirus genus is made up of viruses that are either mosquito-borne, tick-borne and other viruses transmitted by unknown vectors. Flaviviruses present a significant threat to global health and infect up to 400 million of people annually. As the climate continues to change throughout the world, these viruses have become prominent infections with increasing number of infections being detected beyond tropical borders. These include Dengue virus (DENV), West Nile virus (WNV), Japanese encephalitis virus (JEV) and Zika virus (ZIKV). Several highly conserved epitopes of flaviviruses had been identified and reported to interact with antibodies which lead to cross-reactivity results. The major interest of this review paper is mainly focused on the serological cross-reactivity between DENV serotypes, ZIKV, WNV, and JEV. Direct and molecular techniques are required in the diagnosis of flavivirus associated human disease. In this review, the serological assays such as neutralization tests, enzyme-linked immunosorbent assay, haemagglutination-inhibition test, Western blot test, and immunofluorescence test will be discussed. Serological assays that have been developed are able to detect different immunoglobulin isotypes (IgM, IgG, and IgA), however it is challenging when interpreting the serological results due to the broad antigenic cross-reactivity of antibodies to these viruses. However the neutralization tests is still considered as the gold standard to differentiate these flaviviruses.